2001
DOI: 10.1051/0004-6361:20010650
|View full text |Cite
|
Sign up to set email alerts
|

The Lyαforest at $\mathsf{1.5 < {\vec z} < 4}$

Abstract: Abstract. Using high resolution (R ∼ 45 000), high S/N (∼20-50) VLT/UVES data, we have analyzed the Lyα forest of 3 QSOs in the neutral hydrogen (H i) column density range NH i = 10 12.5−16 cm −2 at 1.5 < z < 2.4. We combined our results with similar high-resolution, high S/N data in the literature at z > 2.4 to study the redshift evolution of the Lyα forest at 1.5 < z < 4. We have applied two types of analysis: the traditional Voigt profile fitting and statistics on the transmitted flux. The results from both… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
191
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(211 citation statements)
references
References 82 publications
18
191
2
Order By: Relevance
“…The values of the K-S probability show that the power law is an excellent approximation of the distribution of lines at the redshift range covered in our sample. Note that this disagrees with the result of Kim, Cristiani, & D'Odorico (2001), who found that the break in dN=dz slope occurred around z $ 1:2.…”
Section: The Methodscontrasting
confidence: 99%
See 1 more Smart Citation
“…The values of the K-S probability show that the power law is an excellent approximation of the distribution of lines at the redshift range covered in our sample. Note that this disagrees with the result of Kim, Cristiani, & D'Odorico (2001), who found that the break in dN=dz slope occurred around z $ 1:2.…”
Section: The Methodscontrasting
confidence: 99%
“…Analyses of high-redshift data (Petitjean et al 1993;Press & Rybicki 1993;Hu et al 1995;Dobrzycki & Bechtold 1996;Kim et al 2001) showed that the value of is in the 1.4-1.7 range. Analysis of low-redshift data from HST/GHRS (Penton et al 2000) indicated near the high end of this range, at 1.7-1.8.…”
Section: Line Equivalent Width and Neutral Hydrogen Column Density DImentioning
confidence: 99%
“…The result from the HST/FOS Quasar Absorption Line Key project shows such a slow change in the dn/dz evolution at z < 1.5 (Weymann et al 1998), compared to a much steeper dn/dz evolution shown at z > 2 ( Kim et al 1997Kim et al , 2001Kim et al , 2002. Cosmic variance also seems to increase at lower z .…”
Section: Introductionmentioning
confidence: 91%
“…The data reduction and analysis for HE 2217À2818 have been described by Kim, Cristiani, & D'Odorico (2001), who also show part of the spectrum. Some spectral regions and results for HE 1122À1648 are described by Kim et al (2002).…”
Section: Observations and Absorption Line Fitsmentioning
confidence: 99%